2017
DOI: 10.1016/j.brachy.2016.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Skin surface brachytherapy: A survey of contemporary practice patterns

Abstract: Purpose The aim of this study was to define current patterns of care among radiation oncologists who utilize skin surface brachytherapy for the treatment of cutaneous squamous cell carcinoma (cSCC) and basal cell carcinoma (BCC) in academic and community settings. Methods and materials A 30 question electronic survey was administered to clinician members of the American Brachytherapy Society. The respondents were asked to provide details regarding their clinical practice and their approach to skin surface br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(15 citation statements)
references
References 20 publications
(17 reference statements)
0
15
0
Order By: Relevance
“…The recent advent of electronic brachytherapy, in addition to the long‐standing use of radionuclide brachytherapy, has made the delivery of brachytherapy safer and broadened its popularity as a modality to non‐surgically treat patients with NMSC, especially in the US. In a recent US‐based survey sent to clinicians utilizing brachytherapy (any type) to treat NMSC, the delivery of hypofractionation was the preferred approach with many clinicians comfortable prescribing up to 7 Gy fractions in select clinical scenarios . In two recent studies, the local control rates with cutaneous brachytherapy were both 99% respectively …”
Section: Discussionmentioning
confidence: 99%
“…The recent advent of electronic brachytherapy, in addition to the long‐standing use of radionuclide brachytherapy, has made the delivery of brachytherapy safer and broadened its popularity as a modality to non‐surgically treat patients with NMSC, especially in the US. In a recent US‐based survey sent to clinicians utilizing brachytherapy (any type) to treat NMSC, the delivery of hypofractionation was the preferred approach with many clinicians comfortable prescribing up to 7 Gy fractions in select clinical scenarios . In two recent studies, the local control rates with cutaneous brachytherapy were both 99% respectively …”
Section: Discussionmentioning
confidence: 99%
“…There are several techniques of radiotherapy, each having advantages and disadvantages. A recent survey study completed by 16 members of American Brachytherapy Society indicated that the majority of them prefer brachytherapy over external beam radiation therapy given the shorter treatment course, conformity of treatment for irregular or curved targets and shallow dose deposition [ 176 ]. Many of them routinely use ultrasound to estimate the depth and lateral extension of the lesion before initiating treatment, which has shown to be helpful for more accurate treatment planning [ 176 , 177 ].…”
Section: Treatment Of Nmsc: Overview Of Surgical and Non-surgical mentioning
confidence: 99%
“…A recent survey study completed by 16 members of American Brachytherapy Society indicated that the majority of them prefer brachytherapy over external beam radiation therapy given the shorter treatment course, conformity of treatment for irregular or curved targets and shallow dose deposition [ 176 ]. Many of them routinely use ultrasound to estimate the depth and lateral extension of the lesion before initiating treatment, which has shown to be helpful for more accurate treatment planning [ 176 , 177 ]. The advantage of superficial radiotherapy (SRT) is that the maximum dose is at skin’s surface, and there is less penetration through eye shields, thus making it easier to use around the eye [ 178 ].…”
Section: Treatment Of Nmsc: Overview Of Surgical and Non-surgical mentioning
confidence: 99%
“…There are no available studies that assess the frequency of errors or the setup accuracy in fractionated treatment regimens, but the proposed methodology can potentially simplify the procedure and may reduce setup variations and errors. Reducing practice variations is crucial to advance the field of skin HDR‐BT.…”
Section: Discussionmentioning
confidence: 99%